Amale Sodhlin Ni Khoi Choro Bhano : Context analysis of the song - Adhikari, Anil (Adhyayan Journal, 2023)
This article examines the context of the song Amale Sodhlin Ni Khoi Choro Bhano. Physical, personal, and cognitive context have been chosen as the primary research problems for this article. This article is a library work that was compiled using a qualitative research methodology and analytic framework. It is based on a theoretical analysis of reference analysis. Contextual analysis is a discipline that analyzes text based on the context that language creates in a linguistic structure that is higher than the paragraph level. In the presented song compilation, the counter-revolution, which has been continuously dynamic since the 2007 political change in Nepal, and the memories of a war-wounded soldier before his death are depicted.